ÍNDICE DE DEGRADAÇÃO AMBIENTAL DA BACIA HIDROGRÁFICA DO ARROIO OLARIAS, EM PONTA GROSSA – PR, ENTRE 1980 E 2005 - Rogalski, Sergio Ricardo (2011)
This study aims to identify the degree of environmental degradation of the watershed of the stream Olarias in the city of Ponta Grossa - Paraná, between the years of 1980 and 2005, using the methodology of the Index of Environmental Degradation - IDA. The city of Ponta Grossa has 12 small urban watersheds. This river system has a radial drainage pattern, expressed by four (4) main stream: Olarias, Pilão de Pedra, Ronda and Madureira, whose sources are located or in the commercial center of the town or close to it, heading in different directions to urban area. The watershed of the stream Olarias has an area of 2,711.77 hectares with an approximated population of 70,099 inhabitants according to IBGE census (2000). Being an urban watershed the use of this methodology was relevant to this study. The IDA model uses elements of the natural and also inserts into its formutation the anthropic factor, represented by the population density. Besides the fact that it lists the representation of anthropic values, it is based on the vegetation, soil and slope factors, which all provides classification parameters that wuantify the degree of environmental degradations, represented by four classes of environmental quality: high environmental quality, moderate environmental quality, sub – critical environmetal quality and critical environmetal quality. Supported by datas provided through na analysis of time –space by the geotecnologies, the result of the IDA for 2005 showed that the environmetal state of the watershed of the stream of Olarias was represented by only three classes. The class of Critical Environmental was seen in 67,18% of the stream area, the Sub – Critical Environmetal classon 20,64% and the Moderate Environmetal Class on 12,18%. The IDA for 1980 showed, instead, four environmetal classes. The class related with High Environmental Quality was represented by 10.18% of the total watershed area, followed by Moderate Environmetal class with 25,25%. The Sub – Critical Environmental class represented 44,13%, being the most significant in this period, and at last, the Critical Environmetal class with 20,49%. The use of IDA allowed an environmetal diagnosys, which promotes academic discussions, as on the point of view of modeling the environment, as granting subsidies to management by the government.